2015
DOI: 10.1097/mca.0000000000000260
|View full text |Cite
|
Sign up to set email alerts
|

Low serum testosterone level was associated with extensive coronary artery calcification in elderly male patients with stable coronary artery disease

Abstract: Our findings indicate an inverse association between testosterone level and the susceptibility to extensive CAC in elderly men with stable CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…A total of 884 studies were identified. After exclusion of duplicates and review of the retrieved papers for the above criteria (the selection process is shown in Figure 1 ), 10 studies comprising 15,769 symptomatic patients [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] were eligible for inclusion in the systematic review, while seven studies comprising 12,682 patients [ 10 , 11 , 12 , 14 , 16 , 17 , 18 ] were eligible for inclusion in the meta-analysis. All are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 884 studies were identified. After exclusion of duplicates and review of the retrieved papers for the above criteria (the selection process is shown in Figure 1 ), 10 studies comprising 15,769 symptomatic patients [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] were eligible for inclusion in the systematic review, while seven studies comprising 12,682 patients [ 10 , 11 , 12 , 14 , 16 , 17 , 18 ] were eligible for inclusion in the meta-analysis. All are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The papers were then divided according to CAC assessment type (i.e., CAC presence, extent or progression). One study, Lai et al [ 10 ], assessed both CAC presence and extent and is, consequently, shown twice in both the systematic review and meta-analysis, while studies by Mayer et al [ 11 ] and Mitsutake et al [ 12 ] could be used for both CAC presence and extent in the meta-analysis but were used only for CAC extent in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Multiple studies reveal an inverse association between testosterone levels and coronary artery calcium (CAC) scores. 49,50 There have also been studies suggesting that testosterone levels serve as an independent predictor of CAD severity when assessed via Gensini score. 8 Studies involving men younger than 45 years with premature CAD have also found low testosterone levels in patients with CAD compared with controls.…”
Section: Testosterone and Cadmentioning
confidence: 99%
“…Similarly, Mitsutake et al 8 found that in 535 patients age, male sex and HT were associated with CAC extent, while DL and DM were not associated but Tanaka et al 14 found that age, male sex, HT, DM were associated in 1363 patients, while obesity, smoking and DL were not. Additionally, using a cut-off of ≥ 400, Lai et al 15 found that in 210 patients, none of the conventional CV risk factors correlated with a higher CAC score. Our patient group of 6309 was considerably larger than the cohort size in any of these studies but there is little agreement either between these studies or with our findings, except to demonstrate the importance of age and male sex.…”
Section: Comparison With Other Studies Investigating Cac Extentmentioning
confidence: 99%